2016
DOI: 10.1155/2016/3269405
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics‐Based Identification of the Molecular Signatures of Liver Tissues from Aged Rats following Eight Weeks of Medium‐Intensity Exercise

Abstract: Physical activity has emerged as a powerful intervention that promotes healthy aging by maintaining the functional capacity of critical organ systems. Here, by combining functional and proteomics analyses, we examined how hepatic phenotypes might respond to exercise treatment in aged rats. 16 male aged (20 months old) SD rats were divided into exercise and parallel control groups at random; the exercise group had 8 weeks of treadmill training with medium intensity. Whole protein samples of the liver were extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…The effects of exercise on liver metabolism are becoming increasingly well described [ 56 ] and include increased mitochondrial content and glycolysis, and reduced expression of lipid synthesis proteins [ 57 , 58 ], which is associated with partial resolution of hepatic steatosis [ 7 ]. Furthermore, transcriptomic analysis conducted in the liver of mice immediately after an acute bout of exercise revealed marked increases in the expression of genes involved in mitogen-activated protein kinase (MAPK) and PPAR signalling, and fatty acid metabolism [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of exercise on liver metabolism are becoming increasingly well described [ 56 ] and include increased mitochondrial content and glycolysis, and reduced expression of lipid synthesis proteins [ 57 , 58 ], which is associated with partial resolution of hepatic steatosis [ 7 ]. Furthermore, transcriptomic analysis conducted in the liver of mice immediately after an acute bout of exercise revealed marked increases in the expression of genes involved in mitogen-activated protein kinase (MAPK) and PPAR signalling, and fatty acid metabolism [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, transcriptomic analysis conducted in the liver of mice immediately after an acute bout of exercise revealed marked increases in the expression of genes involved in mitogen-activated protein kinase (MAPK) and PPAR signalling, and fatty acid metabolism [ 17 ]. However, whether such acute changes lead to stable adaptations at the protein level is not well defined [ 58 ]. To address this knowledge gap, we performed unbiased assessment of the hepatocyte proteome following chronic exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . reported that SOD activity and GSH were significantly raised after rats were exercised at medium intensity (24). Radak et al .…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al also showed high-intensity exercise might induce oxidative stress 31 . Li et al reported that SOD activity and GSH were significantly raised after rats were exercised at medium intensity 32 . Radak et al also indicated that moderate exercise significantly increased the activity of antioxidant enzymes 33 .…”
Section: The Impact Of Different Exercise Training Intensities On The...mentioning
confidence: 99%